Studi Kasus Pembelajaran Mendalam (Deep Learning) pada Pemahaman Konsep Matematika Siswa - Maman, Maman; Dewanto, Tito Adi; Koerniawan, Iwan; Dewi, Cristiana; Husna, Nina; Murni, Sri; Arfatin N, Arfatin N (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze the implementation of Deep Learning pedagogy in enhancing students’ conceptual understanding and learning engagement in eighth-grade mathematics classrooms. The study employed a qualitative case study design supported by descriptive quantitative data and was conducted in a public junior high school in North Jakarta. Data were collected through classroom observations, interviews, and a 17-item Likert-scale questionnaire administered to students. The findings indicate that students generally responded positively to the implementation of Deep Learning, particularly in terms of interaction and collaboration, which fostered a more dialogic and supportive learning environment. Although improvements in conceptual understanding and learning motivation were observed, deeper conceptual restructuring requires stronger instructional scaffolding and metacognitive reflection. In conclusion, Deep Learning pedagogy has strong potential to support student-centered mathematics learning by promoting active engagement and meaningful understanding, provided that it is implemented systematically and sustainably.   Keywords: Conceptual Understanding, Deep Learning, Learning Engagement, Mathematics Education, Students’ Perception